Extracellular microRNA profiling for prognostic prediction in patients with high‐grade serous ovarian carcinoma. Issue 12 (19th October 2021) - Yoshida, Kosuke; Yokoi, Akira; Matsuzaki, Juntaro; Kato, Tomoyasu; Ochiya, Takahiro; Kajiyama, Hiroaki; Yamamoto, Yusuke
Abstract: High‐grade serous ovarian carcinoma is a leading cause of death in female patients worldwide. MicroRNAs (miRNAs) are stable noncoding RNAs in the peripheral blood that reflect a patient's condition, and therefore, they have received substantial attention as noninvasive biomarkers in various diseases. We previously reported the usefulness of serum miRNAs as diagnostic biomarkers. Here, we investigated the prognostic impact of the serum miRNA profile. We used the GSE106817 dataset, which included preoperative miRNA profiles of patients with ovarian malignancies. Excluding patients with other malignancy or insufficient prognostic information, we included 175 patients with high‐grade serous ovarian carcinoma. All patients except four underwent surgery and received chemotherapy as initial treatment. The median follow‐up period was 54.6 months (range, 3.5‐144.1 months). Univariate Cox regression analysis revealed that higher levels of miR‐187‐5p and miR‐6870‐5p were associated with both poorer progression‐free survival (PFS) and overall survival (OS), and miR‐1908‐5p, miR‐6727‐5p, and miR‐6850‐5p were poor prognostic indicators of PFS. The OS and PFS prognostic indices were then calculated using the expression values of three prognostic miRNAs. Multivariate Cox regression analysis showed that both indices were significantly independent poor prognostic factors (hazard ratio for OS and PFS, 2.343 [ P  = .015] and 2.357 [ P  = .005], respectively). In conclusion, circulating miRNA profiles can potentially provide information to predict the prognosis of patients with high‐grade serous ovarian carcinoma. Therefore, there is a strong demand for early clinical application of circulating miRNAs as noninvasive biomarkers. Abstract : We showed that several circulating microRNAs were useful as predictive biomarkers in patients with high‐grade serous ovarian carcinoma. This study and our previous report indicated that circulating microRNA profiles can be useful clinical tools for a highly accurate diagnosis and prognostic prediction using a single blood test.